INTRODUCTION OF ICT TO RESHAPE PUBLIC INSTITUTIONS IN RURAL AREAS - Yakasai, B. A. (Farabi Journal of Social Sciences, 2022)
With the trend in ICT and the Internet in the 21st century, government related services and public service delivery are becoming more accessible and easier to receive virtually. But the question is; are they available generally in and around the whole appropriate nation or country? Here comes the question this paper sort to answer. The unavailability of ICT in some public institutions in rural areas is still a challenge even as information and communication technology is widely accessible in our current world. Studies prove embracing e-government by various countries is an outstanding accomplishment, but extending this success to remote and rural regions is the prospect triumph that needs to be worked on especially in the current digital century. Considering the role digital technology is playing in human social life as an essential factor of modernization and a century development. Introducing a wide accessible ICT resources in rural areas could mean a milestone for developing states. Although we may acknowledge some challenges in the process like illiteracy, lack of proper infrastructure and insufficient professionals in the rural areas, we should as well glance at the brighter part that ICT would influence, like some basic social sectors that consist education, economy, health and employment. Keywords: ICT, rural areas, public institutions, service delivery, society.